IMPLEMENTATION OF MULTIPLE INTELLIGENCE IN ELEMENTARY SCHOOL OR MADRASAH IBTIDAIYAH LEARNING - Karwadi, Karwadi (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to describe the implementation of multiple intelligences in learning in SD/MI. This research is qualitative and uses library research. Data collection is done by seeking information from literature or writing contained in various written sources through documentation studies. Data analysis was carried out using an analytical-descriptive approach, that is, after the data was collected, it was explained according to the problems studied, interpreted, and concluded. The results showed that learning from the point of view of multiple intelligences is a concrete form of humanistic education and highly values diversity. In this context, all students are seen as having the opportunity to succeed in learning. Teachers have a great responsibility to help students find suitable learning paths. The conclusion of this study is that the application of multiple intelligences in learning has broad implications for curricula, educational institutions, and human resources involved in education.